Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Profile Matching - Yogi Bachtiar (Faktor Exacta, 2022)
Teachers are a big foundation in education in Indonesia, without teachers we all will not be smart. There is a need for great respect for teachers, both from the government and schools. There is a need for great respect for teachers, both from the government and schools. teaching teachers must pay attention and give appreciation to teachers so that teachers become enthusiastic in teaching activities. Many teachers have achievements. In giving assessment criteria, subjective ones are often used with good, sufficient and insufficient comparisons so that the teacher's assessment is deemed inappropriate or objective with reality. used to assist decision making. In this paper, a decision support system was chosen using the profile matching method. It is hoped that the teacher selection process can be carried out quickly and accurately)